2017
DOI: 10.1021/acs.estlett.7b00267
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Biochar: A Workplace Safety Concern?

Abstract: Biochar has a number of environmental applications, including soil amendment for agriculture, remediation of contaminated soils and sediments, and climate change mitigation. Dust formed during its production and field application may pose a health risk, but the cytotoxicity of biochar has, to the best of our knowledge, not previously been investigated. Therefore, we measured the concentration-dependent cytotoxicity of biochar on an NIH 3T3 mouse fibroblast cell line. We used a contaminant trap experiment to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Apart from (bio)chemical transformation, cells can also physically interact with CNPs including soot, [86][87][88] biochar particles, 89 and CNTs. 90,91 In such cases the CNPs are immobilized by aggregation or ingestion, while at the same time inducing negative biological effects on the cells (such as cytotoxicity).…”
Section: Biological Transformationmentioning
confidence: 99%
“…Apart from (bio)chemical transformation, cells can also physically interact with CNPs including soot, [86][87][88] biochar particles, 89 and CNTs. 90,91 In such cases the CNPs are immobilized by aggregation or ingestion, while at the same time inducing negative biological effects on the cells (such as cytotoxicity).…”
Section: Biological Transformationmentioning
confidence: 99%
“…The understanding that biochar is a heterogeneous aggregation of particles with different sizes that have gradually replaced the previous recognition (Zhang et al 2019). Beside bulk biochar, small-sized biochar (dissolved and nanometer-scale biochar) has also been found to be an important component of biochar (Kang et al 2015;Lian and Xing 2017;Oleszczuk et al 2016;Saxena et al 2014;Sigmund et al 2017;Spokas et al 2014;Wang et al 2012Wang et al , 2013Yue et al 2019;Zhang et al 2019).…”
Section: Macroscopic: Bulk Biochar Dissolved and Nano-biocharmentioning
confidence: 99%
“…Therefore, the workplace should be well ventilated. Sigmund et al [165] investigated the cytotoxicity of biochar and reported that cytotoxic effects were likely related to its particulate nature and size distribution. They also suggested that, to minimize the risk of exposure, operators should wear respiratory protective equipment during biochar production and its application in the field.…”
Section: Safety Measures During Biochar Production and Its Applicationsmentioning
confidence: 99%